Living Phenomenology as a Decolonial Practice - Lewis R. Gordon (Philosophies)
This paper examines phenomenology as a living form of thought with significance for decolonial epistemic practice. After discussing how phenomenology addresses concerns of living thought, the author outlines disciplinary decadence as a form of colonial epistemic practice and offers his theory of teleological suspensions of disciplinarity among the decolonial epistemic practices that could be devoted not only to the decolonization of thought but also ideas pertaining to normative life.